The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2106/jbjs.rvw.21.00166
|View full text |Cite
|
Sign up to set email alerts
|

Klippel-Feil Syndrome

Abstract: Klippel-Feil syndrome (KFS) is a rare multisystem constellation of findings with congenital cervical fusion as the hallmark. The etiology is not fully understood.» Recent studies have indicated that KFS is more prevalent than previously described.» Hypermobility in the nonfused segments may lead to adjacent segment disease and potential disc herniation and myelopathy after minor trauma.» Most patients with KFS are asymptomatic and can be managed nonoperatively. Surgical treatment is reserved for patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
1
6
0
2
Order By: Relevance
“…KFS is a rare congenital abnormality characterized by fusion of at least one pair of adjacent cervical vertebrae, often resulting in a shortened neck, lower hairline, and limited neck mobility [ 7 ]. Our patient had all the three features and had evidence of Sprengel’s deformity [ 6 ]. Samartzis et al classified KFS into three different types (types I–III) on the basis of the extent of cervical fusion; this classification system is widely used to study the prognosis of such patients [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…KFS is a rare congenital abnormality characterized by fusion of at least one pair of adjacent cervical vertebrae, often resulting in a shortened neck, lower hairline, and limited neck mobility [ 7 ]. Our patient had all the three features and had evidence of Sprengel’s deformity [ 6 ]. Samartzis et al classified KFS into three different types (types I–III) on the basis of the extent of cervical fusion; this classification system is widely used to study the prognosis of such patients [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had all the three features and had evidence of Sprengel’s deformity [ 6 ]. Samartzis et al classified KFS into three different types (types I–III) on the basis of the extent of cervical fusion; this classification system is widely used to study the prognosis of such patients [ 6 , 8 ]. Type I involves single-level congenital fusion of cervical segment; type II comprises multiple, noncontiguous congenitally fused segments; and type III includes multiple, contiguous congenitally fused cervical segments [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…R ecently, Hachem et al found that Chiari malformation represented the third most common phenotype in patients with KFS (and was particularly common in those cases in which the upper cervical spine was involved) undergoing a surgical procedure, as shown by principal component analysis 13 . In a review by Jae-Min Park et al on patients with KFS, those with craniocervical abnormalities were considered to be at increased risk for spinal cord injury 14 . Sakamoto et al reported on a patient with sandwich fusion and AAD, a retro-odontoid pseudotumor, and intramedullary hyperintensity 15 .…”
Section: Discussionmentioning
confidence: 99%